2017
DOI: 10.1200/jco.2017.72.4963
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization Rates and Predictors of Rehospitalization Among Individuals With Advanced Cancer in the Year After Diagnosis

Abstract: Among individuals with advanced cancer, frequent hospitalization increasingly is viewed as a hallmark of poor-quality care. We examined hospitalization rates and individual-and hospital-level predictors of rehospitalization among individuals with advanced cancer in the year after diagnosis. MethodsIndividuals diagnosed with advanced breast, colorectal, non-small-cell lung, or pancreatic cancer from 2009 to 2012 (N = 25,032) were identified with data from the California Cancer Registry (CCR).After linkage with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 36 publications
5
61
1
Order By: Relevance
“…28 Less intensive care and fewer invasive procedures are considered corollary metrics of quality end-of-life care. 39,40 Taken together, these results suggest PC involvement is correlated with less intensive medical therapy at the end of life. Due to the cross-sectional nature of this study, we were unable to determine whether PC causes less intensive care and lower inpatient costs per se.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…28 Less intensive care and fewer invasive procedures are considered corollary metrics of quality end-of-life care. 39,40 Taken together, these results suggest PC involvement is correlated with less intensive medical therapy at the end of life. Due to the cross-sectional nature of this study, we were unable to determine whether PC causes less intensive care and lower inpatient costs per se.…”
Section: Discussionmentioning
confidence: 73%
“…One other study examined the PC cost for US children with any chronic condition and reported savings of $2458 per day for patients who received PC ( P < .0001) . Less intensive care and fewer invasive procedures are considered corollary metrics of quality end‐of‐life care . Taken together, these results suggest PC involvement is correlated with less intensive medical therapy at the end of life.…”
Section: Discussionmentioning
confidence: 97%
“…(46,47) One used this indicator to analyse the rate of hospital admissions through the ED in the year following a diagnosis of breast, colorectal, non-small cell lung or pancreatic cancer. (48) Overall, indicators of access to outpatient care and particularly ED visits and emergency admission and ACSCs ED visits/ACSCs emergency admissions were the most frequent indicators used across studies.…”
Section: Equity Indicatorsmentioning
confidence: 99%
“…Insurance coverage as a relevant SEDH was approached in diverse ways amongst the 16 articles that used it including comparing outcomes between uninsured and insured individuals, (24,30) between publicly and privately insured individuals, (33,(38)(39)(40)46,49) or between uninsured, publicly and privately insured individuals. (23,25,35,(41)(42)(43)47,48) Present in more than half (55%) of the studies analysed, it is the most widely used SEDH in analyses of health care equity identi ed in this review. (It re ects the ability to pay in Levesque's framework).…”
Section: A Insurance Statusmentioning
confidence: 99%
See 1 more Smart Citation